Estudo eletroquímico e eletroanalítico da microcistina-LR e avaliação in situ da sua interação com DNA - Lopes, Ilanna Campelo (2011)
The Microcystin-LR (MC-LR) is a cyclic heptapeptidic hepatotoxin most toxic to the human and animal health and is the most commonly found in cyanobacteria blooms. Moreover, it can induce oxidative damage to DNA, leading possibly to the carcinogenicity in humans. In this study, MC-LR was investigated on glassy carbon electrode using voltammetric techniques. It was observed that the oxidation of MC-LR is an irreversible, diffusion controlled and pH-independent process. This toxin was chemically degradated in buffer solution along the time, with homogeneous formation of two electroactive degradation products. These degradation products have undergone an irreversible and pH-dependent oxidation process, leading to the formation of two oxidation products, which have undergone reversible and pH-dependent reactions. Thus, oxidation reaction mecanisms of MC-LR and its degradation products were proposed. An electroanalytical study for the determination of MC-LR was carried out using DPV. For this, an analytical curve was built in a linear concentration range from 5 to 25 μmol L-1. Based on this curve, detection and quantification limits were estimated at 0.0014 μmol L-1 (1.39 μg L-1) and 0.0046 μmol L-1 (4.57 μg L-1), respectively. In addition, an in situ evaluation of MC-LR-dsDNA interaction was investigated and showed that this toxin interacts and binds to dsDNA chains, inducing conformational changes in the double helix structure along the incubation time.